Context-dependent function of ROS in the vascular endothelium: The role of the Notch pathway and shear stress - Vieceli Dalla Sega, F.; Aquila, G.; Fortini, F.; Vaccarezza, Mauro; Secchiero, P.; Rizzo, P.; Campo, G. (2017)
Reactive oxygen species (ROS) act as signal molecules in several biological processes whereas excessive, unregulated, ROS production contributes to the development of pathological conditions including endothelial dysfunction and atherosclerosis. The maintenance of a healthy endothelium depends on many factors and on their reciprocal interactions; in this framework, the Notch pathway and shear stress (SS) play two lead roles. Recently, evidence of a crosstalk between ROS, Notch, and SS, is emerging. The aim of this review is to describe the way ROS interact with the Notch pathway and SS protecting from-or promoting-the development of endothelial dysfunction.